Serum Proteomics of Older Patients Undergoing Major Cardiac Surgery: Identification of Biomarkers Associated With Postoperative Delirium - Rhee, James; Kuznetsov, Alexandra; McKay, Tina; Lyons, Margaret; Houstis, Nicholas; Mekkonen, Jennifer; Ethridge, Breanna; Ibala, Reine; Hahm, Eunice; Gitlin, Jacob; Guseh, J. Sawalla; Kitchen, Robert; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Postoperative delirium (POD) is an acute altered mental state commonly encountered after cardiac surgery. The pathophysiological mechanisms underlying POD remain unclear. We aimed to identify circulating proteins significantly altered after major cardiac surgery with cardiopulmonary bypass (CPB). We also aimed to enable inferences on associations with POD. Methods: Serum and whole blood samples were collected before CPB (n =16 patients; n = 8 with POD), and again from the same patients on postoperative day one. All patients were clinically evaluated for POD on postoperative days one through three. An aptamer-based proteomics platform (SOMAscan) was used to quantify serum protein abundance in patients with POD compared to non-POD controls. We also performed a lipopolysaccharide (LPS)-based in vitro functional analysis (TruCulture) on whole-blood samples from POD and non-POD patients to approximate surgical stress. Cytokine levels were determined using a multiplexed immunoassay (Luminex). Results: Cardiac surgery with CPB resulted in a significant (padj < 0.01) change in 48.8 % (637 of 1305) of proteins detected by SOMAscan. Gene set enrichment showed that the most impacted biological processes involved myeloid cell activation. Specifically, activation and degranulation of neutrophils were the top five, highest-scoring processes. KEGG pathway analyses showed that metabolic enzymes, particularly those of glycolysis, were elevated in serum concentration after surgery. Several proteins were significantly increased postoperatively in patients diagnosed with POD relative to the non-POD controls, with interleukin-6 (IL-6) showing the greatest fold-change. LPS stimulation of whole blood samples confirmed these findings. Linear regression analysis showed a highly significant correlation between Confusion Assessment Method (CAM) scores and CPB-mediated changes in cGMP-inhibited 3',5'-cyclic phosphodiesterase A (PDE3A). Conclusions: Cardiac surgery with CPB resulted in inflammasome changes accompanied by unexpected increases in metabolic pathways. In exploratory analyses, we found that POD was associated with changes in the expression level of various proteins. Thus, in vivo and in vitro protein biomarkers may advance objective approaches to identify patients at risk for POD preemptively, and also lend insights into the pathophysiological mechanisms underlying POD.